(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This case study examines the critical interplay between climate change and forest fires in the Konkan region of Maharashtra, India. The Konkan region, known for its rich biodiversity and dense forest cover, has been increasingly susceptible to forest fires due to shifting climatic conditions. Climate change has led to prolonged dry spells, increased temperatures, and erratic rainfall patterns, creating a conducive environment for forest fires. These fires pose a significant threat to the region’s flora and fauna, disrupt the ecological balance, and have severe socio-economic impacts on local communities reliant on forest resources. This study delves into the specific impact of climate change on the frequency and intensity of forest fires in the Konkan forests. It analyzes the ecological consequences, including the loss of biodiversity and habitat destruction, as well as the broader environmental ramifications such as increased carbon emissions. Additionally, the study explores the socio-economic repercussions for the indigenous and local populations who depend on the forests for their livelihood and cultural practices. Furthermore, the case study highlights the adaptive measures and mitigation strategies being undertaken to address this escalating issue. It discusses both governmental and community-based initiatives aimed at enhancing forest resilience, improving fire management practices, and promoting sustainable forest use. By focusing on the Konkan region, this study provides valuable insights into the broader implications of climate change on forest ecosystems in India and underscores the urgency of implementing comprehensive and sustainable forest management policies. This case study emphasizes the need for an integrated approach to combat the dual challenges of climate change and forest fires, advocating for collaboration between policymakers, scientists, and local communities to safeguard the ecological and socio-economic well-being of the Konkan region.